Interventional Radiology in Pelvic Trauma - Franco, Derek F.; Zangan, Steven M. (Seminars in Interventional Radiology, 2020)
Traumatic pelvic injuries are associated with high injury severity scores and significant morbidity and mortality. As fractures and ligamentous disruption result in increased pelvic volume, retroperitoneal hemorrhage can spiral and progress to hemorrhagic shock. Due to the extensive collateral supply and limitations of surgery for pelvic hematomas, angiographic treatment is at the forefront of pelvic trauma management. This article will discuss typical injuries seen in pelvic trauma, treatment modalities available to the interventional radiologist, and common angiographic treatment strategies and techniques.
Keywords: pelvic trauma; embolization; angiography; hemorrhage; interventional radiology